Asphalt additive, asphalt composition and preparation method thereof
By using different microcapsules to wrap active components in asphalt additives, the problem of asphalt flue gas emissions in asphalt pavement construction is solved, achieving longer storage and service life and lower environmental pollution.
Patent Information
- Application Number
- CN202311125688.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-09-01
AI Technical Summary
The prior art is difficult to effectively reduce the emission of asphalt flue gas during asphalt pavement construction, resulting in environmental pollution.
A bituminous additive containing different microcapsules is used. By wrapping the active components in the microcapsules, the additive uses different sustained release rates of the microcapsules to extend the acting time of the active components and reduce the emission of asphalt flue gas.
It has achieved effective reduction of asphalt flue gas emissions during asphalt construction, extended the storage and service life of asphalt compositions, and reduced environmental pollution.
Smart Images

Figure BDA0004430077270000281
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of road asphalt, and specifically relates to an asphalt additive and an asphalt composition and a preparation method thereof, and more specifically, relates to a clean asphalt additive and a clean asphalt composition and a preparation method thereof. Background Art
[0002] As the main type of highway, asphalt pavement still uses the traditional hot-mix hot-paving process in its pavement construction. During the construction process, the asphalt will come into contact with oxygen in the air and react: on the one hand, condensation reaction will occur to produce polycyclic aromatic hydrocarbons with larger molecular weight, which will further condense into gums and asphaltene; on the other hand, asphalt molecules will crack under heat conditions to produce compounds with smaller molecular weight. These small molecular compounds will evaporate to form asphalt fumes, which will seriously damage the ecological balance, pollute the surrounding environment and harm human health.
[0003] Given that asphalt pavement releases volatile organic compounds (VOCs) in an unorganized manner during the paving process, it is difficult to collect and control the entire process. It is an urgent issue that needs to be addressed at present to explore how to reduce asphalt fume release at the source, achieve clean asphalt pavement construction, and ensure the harmonious development of the transportation industry and the social economy.
[0004] Chinese patent application CN101842426A reduces the odor of asphalt-like substances by adding an active agent and a diluent, but the active agent added has poor reactivity and a limited action time, and cannot work for a long time.
[0005] Chinese patent application CN109749466A reduces asphalt fume emissions through metal organic framework compounds, inorganic adsorbent materials, reactive odor inhibitors, free radical scavengers, etc., but its inorganic adsorbent materials, etc. have poor compatibility with asphalt, affecting the performance of asphalt. There is also the problem of short action time of active components.
[0006] Chinese patent application CN103242496A discloses a room temperature self-healing thermoplastic polymer material based on multilayer microcapsules and a preparation method thereof. The fourth layer of the multilayer microcapsule wall is paraffin or chlorinated paraffin, which is soluble in asphalt. The third layer of the capsule wall is silicon dioxide or titanium dioxide, which has poor compatibility with asphalt and will affect the performance of asphalt. Therefore, although it can be used for the repair of thermoplastic polymer materials, it is not suitable for asphalt materials.
[0007] In summary, the prior art simply adds inorganic fillers or active components to asphalt, which may lead to the problem of separation and stratification of the inorganic filler and the asphalt, and the problem that the active component has a limited action time and cannot work for a long time. Summary of the invention
[0008] The purpose of the present invention is to overcome the problem that asphalt pavement in the prior art emits asphalt fumes (including volatile organic compounds), thereby causing environmental pollution, and to provide an asphalt additive and an asphalt composition and a preparation method thereof. The asphalt composition using the asphalt additive of the present invention has a long storage and service life, and can effectively reduce the emission of asphalt fumes and reduce environmental pollution during the construction process.
[0009] In order to achieve the above-mentioned objectives, the present invention provides an asphalt additive on the one hand, which contains a first microcapsule, a second microcapsule and a third microcapsule, wherein the first microcapsule, the second microcapsule and the third microcapsule each include a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains an active component, the capsule wall thickness of the first microcapsule is 0.5-2μm, the capsule wall thickness of the second microcapsule is greater than 2μm and less than or equal to 3μm, and the capsule wall thickness of the third microcapsule is greater than 3μm and less than or equal to 5μm.
[0010] Preferably, the mass ratio of the first microcapsule, the second microcapsule and the third microcapsule is 1:(0.25-4):(0.25-4).
[0011] Preferably, in the first microcapsule, the second microcapsule and the third microcapsule, the capsule wall comprises an inner wall layer and an outer wall layer, the inner wall layer is a resin, and the outer wall layer is a rubber material.
[0012] Preferably, the mass ratio of the inner wall layer to the outer wall layer is 2.4-5:1.
[0013] Preferably, the resin is at least one of melamine resin, urea-formaldehyde resin and polymethyl methacrylate, preferably melamine resin.
[0014] Preferably, the rubber material is at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
[0015] Preferably, in the first microcapsule, the second microcapsule and the third microcapsule, the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0016] Y=0.42X 2 -0.92X+T
[0017] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0018] The elastic modulus of the microcapsule is obtained by testing the mechanical properties of the microcapsule using a nanoindenter, and the thickness of the capsule wall is obtained by testing the frozen sections of the microcapsule using a scanning electron microscope.
[0019] Preferably, in the first microcapsule, the mass ratio of the capsule core to the capsule wall is 1:0.9-1.5; in the second microcapsule, the mass ratio of the capsule core to the capsule wall is 1:1.5-2.2; in the third microcapsule, the mass ratio of the capsule core to the capsule wall is 1:2.2-3.
[0020] Preferably, the active component is an inhibitor for inhibiting the release of asphalt smoke, preferably at least one of aldehyde compounds, ketone compounds, alcohol compounds, phenol compounds and ester compounds.
[0021] Preferably, the aldehyde compound is selected from aliphatic aldehydes having carbon atoms greater than or equal to 7 and aromatic aldehydes having carbon atoms greater than or equal to 6, more preferably at least one of p-tolualdehyde, decanal, o-carboxybenzaldehyde, p-isopropylbenzaldehyde, cinnamaldehyde, p-hydroxybenzaldehyde, p-methoxybenzaldehyde, 2-methyl-3-(3,4-methylene-dioxyphenyl)propanal, 3,4-methylenedioxybenzaldehyde, 3-(4-isopropylphenyl)-2-methylpropanal, ethyl vanillin, phenylacetaldehyde, anisaldehyde, nonadiene-2,6-aldehyde, 2,6-dimethyl-2,6-octadienal, vanillin, citronellal, neral, hydroxymethylpentylcyclohexene acetal, p-diethylaminobenzaldehyde and undecenal.
[0022] Preferably, the ketone compound is selected from aliphatic ketones having a carbon number greater than or equal to 8 and aromatic ketones having a carbon number greater than or equal to 8, and more preferably is at least one of 6-methyl-3,5-heptadien-2-one, 2-undecanone, acetophenone, ionone, irone, methylionone, damascenone and dihydrodamascenone.
[0023] Preferably, the alcohol compound is an alcohol having more than 6 carbon atoms, more preferably at least one of cinnamyl alcohol, menthol, cis-3,7-dimethyl-2,6-octadienol, citronellol, geraniol, myrcenol, 2,6,10-trimethyl-2,6,10-dodecatrien-12-ol, lavandulol, benzyl alcohol, 2-phenylethanol, dihydromyrcenol, tetrahydrogeraniol and nerolidol.
[0024] Preferably, the phenolic compound is a phenol having 6 or more carbon atoms, more preferably at least one of thymol, ethyl maltol, methyl maltol, 3-propenyl-6-ethoxyphenol and isoeugenol.
[0025] Preferably, the ester compound is an ester having a carbon number greater than 7, more preferably at least one of methyl salicylate, methyl cinnamate, ethyl cinnamate, ethyl phenylacetate, methyl phenylacetate, geranyl phenylacetate, phenylethyl phenylacetate, isoamyl phenylacetate, benzyl salicylate, p-methylbenzyl acetate, benzyl acetate, isobutyl benzoate, isoamyl salicylate, benzyl cinnamate, phenylethyl cinnamate, linalyl formate, linalyl acetate, linalyl isobutyrate, menthyl acetate, pine acetate and bornyl acetate.
[0026] Preferably, the active component in the first microcapsule is selected from aldehyde compounds and ketone compounds, the active component in the second microcapsule is selected from alcohol compounds and phenol compounds, and the active component in the third microcapsule is selected from ester compounds.
[0027] A second aspect of the present invention provides an asphalt composition, which contains asphalt and the asphalt additive described above.
[0028] Preferably, the content of the asphalt additive is 0.1-2 parts by weight, preferably 0.15-0.6 parts by weight, relative to 100 parts by weight of the asphalt.
[0029] Preferably, the asphalt composition further contains an antioxidant, and the content of the antioxidant is 0.01-0.1 parts by weight relative to 100 parts by weight of the asphalt.
[0030] Preferably, the antioxidant is bis(3,5-tri-tert-butyl-4-hydroxyphenyl) sulfide, p-tert-butyl catechol, 3,5-di-tert-butyl-4-hydroxybenzyl diethylphosphonate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 4,4'-thiobis(6-tert-butyl-3-methylphenol), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5- At least one of trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 2,6-di-tert-butyl-p-methylphenol, 3,5-di-tert-butyl-4-hydroxybenzoic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylic acid, 3-(3,5-dimethyl-4-hydroxyphenyl)acrylic acid, 3-(3,5-dimethoxy-4-hydroxyphenyl)acrylic acid and 3-(3-methoxy-4-hydroxyphenyl)acrylic acid.
[0031] Preferably, the asphalt is at least one of straight-run asphalt, polymer-modified asphalt and natural asphalt.
[0032] Preferably, the needle penetration of the asphalt is 30-210 1 / 10mm.
[0033] The third aspect of the present invention provides a method for preparing the above-mentioned asphalt composition, the method comprising:
[0034] (1) The first microcapsule, the second microcapsule and the third microcapsule are prepared respectively, and the preparation process is as follows:
[0035] S1, mixing the active ingredient, emulsifier and water to form an oil-in-water emulsion;
[0036] S2, reacting the oil-in-water emulsion with a resin prepolymer, and then filtering, washing, and drying to obtain a pre-coated material;
[0037] S3, in the presence of a volatile solvent, mixing the rubber material with the pre-coated material, then mixing the obtained mixture with water, and heating until the volatile solvent evaporates to obtain microcapsules;
[0038] (2) Mixing molten asphalt, the first microcapsules, the second microcapsules, the third microcapsules and an optional antioxidant.
[0039] Preferably, in step S1, the mass ratio of the active component, the emulsifier and water is 1:(0.05-0.09):(6-9).
[0040] Preferably, in step S2, before the oil-in-water emulsion reacts with the resin prepolymer, the pH value of the oil-in-water emulsion is adjusted to below 5, preferably 2-4.
[0041] Preferably, in step S2, the resin prepolymer is a melamine resin prepolymer.
[0042] Preferably, the preparation method of the melamine resin prepolymer comprises: mixing and dissolving melamine and formaldehyde solution with water, adjusting the pH value to 7.5-9.5, and then placing in a constant temperature water bath at 60-90° C. and reacting for 0.5-3.5 hours under stirring.
[0043] Preferably, the concentration of the formaldehyde solution is 30-40 wt.%.
[0044] Preferably, the mass ratio of the melamine, the formaldehyde solution and the water is 1:(2-3):(8-10).
[0045] Preferably, in step S3, the mass ratio of the rubber material, the volatile solvent and water is 1:(10-20):(50-150).
[0046] Preferably, the emulsifier is selected from at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, cetyltrimethylammonium chloride, cetyltrimethylammonium bromide, cetyldimethylhydroxyethylammonium chloride, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether and hexadecane polyoxyethylene ether.
[0047] Preferably, the volatile solvent is selected from at least one of carbon tetrachloride, dichloromethane and trichloroethylene.
[0048] In the asphalt additive of the present invention, by combining three microcapsules with different sustained-release rates, different active components can be released at different sustained-release rates, thereby extending the action time of the active components. The asphalt additive is used in an asphalt composition, so that the asphalt composition has a longer storage and service life, and during the construction process, the emission of asphalt fume can be effectively reduced, thereby reducing pollution to the environment.
[0049] In a preferred embodiment, the active component in the capsule core of the microcapsule is selected as an inhibitor for inhibiting the release of asphalt smoke, and the capsule wall includes an inner wall layer and an outer wall layer, the inner wall layer is a resin, and the outer wall layer is a rubber material. The rubber material of the outer wall layer is wrapped outside the inner wall layer in the form of a layer of uniform and dense film material, so that the microcapsule as a whole can ensure a certain strength and can be effectively integrated with asphalt, and has good compatibility. DETAILED DESCRIPTION
[0050] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0051] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0052] The asphalt additive described in the present invention contains a first microcapsule, a second microcapsule and a third microcapsule, wherein the first microcapsule, the second microcapsule and the third microcapsule each include a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains active components, the capsule wall thickness of the first microcapsule is 0.5-2μm, the capsule wall thickness of the second microcapsule is greater than 2μm and less than or equal to 3μm, and the capsule wall thickness of the third microcapsule is greater than 3μm and less than or equal to 5μm.
[0053] In the first microcapsule, the second microcapsule and the third microcapsule, the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0054] Y=0.42X 2 -0.92X+T
[0055] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0056] The elastic modulus of the microcapsule is obtained by testing the mechanical properties of the microcapsule using a nanoindenter, and the thickness of the capsule wall is obtained by testing the frozen sections of the microcapsule using a scanning electron microscope.
[0057] In the asphalt additive described in the present invention, in the first microcapsule, the mass ratio of the capsule core to the capsule wall is 1:0.9-1.5; in the second microcapsule, the mass ratio of the capsule core to the capsule wall is 1:1.5-2.2; in the third microcapsule, the mass ratio of the capsule core to the capsule wall is 1:2.2-3.
[0058] In the microcapsule, the thickness of the capsule wall can be 0.5-5 μm, specifically, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm , 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm m, 3.8μm, 3.9μm, 4μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm or 5μm.
[0059] In the microcapsule, the size of the microcapsule may be 50 μm or less, preferably 20 μm or less, and more preferably 3-15 μm.
[0060] In the microcapsule, in a preferred case, the capsule wall includes an inner wall layer and an outer wall layer, the inner wall layer is a resin, and the outer wall layer is a rubber material. In this preferred case, on the one hand, the microcapsule has a certain strength to meet the requirements of road use; on the other hand, the rubber material as the outer wall layer can be effectively integrated with asphalt, and the rubber material has good adhesion and forms a strong bond with the resin (especially melamine resin) as the inner wall layer.
[0061] Further preferably, the mass ratio of the inner wall layer to the outer wall layer is 2.4-5:1, specifically, for example, it can be 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1 or 4:1.
[0062] When the capsule wall of the microcapsule includes an inner wall layer and an outer wall layer, in the first microcapsule, the mass ratio of the capsule core, the inner wall layer and the outer wall layer is 1:(0.7-1):(0.2-0.3); in the second microcapsule, the mass ratio of the capsule core, the inner wall layer and the outer wall layer is 1:(1.2-1.5):(0.4-0.5); in the third microcapsule, the mass ratio of the capsule core, the inner wall layer and the outer wall layer is 1:(1.7-2):(0.6-0.7).
[0063] In the present invention, the content of the capsule core, the content of the capsule wall, and the mass of the inner layer and the outer layer of the capsule wall of the microcapsule are detected by the following method: the microcapsule is added to a volatile solvent (the volatile solvent can be selected from one or more of carbon tetrachloride, dichloromethane and trichloroethylene), and after fully dissolving and filtering, the first solid powder obtained is fully dried, and the difference between the mass of the first solid powder and the initial microcapsule is the mass of the capsule wall outer layer; the first solid powder obtained is further fully ground, added to toluene, and after fully dissolving and filtering, the second solid powder obtained is fully dried, and the difference between the mass of the first solid powder and the first solid powder is the mass of the capsule core; the mass of the inner layer of the capsule wall is the mass of the microcapsule minus the mass of the outer layer of the capsule wall and the mass of the capsule core.
[0064] In the microcapsule, the resin may be at least one of melamine resin, urea-formaldehyde resin and polymethyl methacrylate, and is most preferably melamine resin.
[0065] In the microcapsule, the rubber material may be at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
[0066] In the microcapsule, the active component is preferably an inhibitor for inhibiting the release of asphalt smoke. When the active component in the microcapsule is an inhibitor for inhibiting the release of asphalt smoke, the structure of the microcapsule can prolong the action time of the active component, so that the asphalt composition has a longer storage and service life, and can effectively reduce the emission of asphalt smoke and reduce pollution to the environment during the asphalt construction process.
[0067] In the present invention, the inhibitor for inhibiting the release of asphalt smoke is preferably at least one of aldehyde compounds, ketone compounds, alcohol compounds, phenol compounds and ester compounds.
[0068] In the present invention, the aldehyde compound may be at least one of a fatty aldehyde having a carbon number greater than or equal to 7 and an aromatic aldehyde having a carbon number greater than or equal to 6. In a preferred case, the aldehyde compound is at least one of a fatty aldehyde of C7-C13 and an aromatic aldehyde of C6-C13. Specifically, the aldehyde compound is selected from at least one of p-methylbenzaldehyde, decanal, o-carboxybenzaldehyde, p-isopropylbenzaldehyde, cinnamaldehyde, p-hydroxybenzaldehyde, p-methoxybenzaldehyde, 2-methyl-3-(3,4-methylene-dioxyphenyl)propanal, 3,4-methylenedioxybenzaldehyde, 3-(4-isopropylphenyl)-2-methylpropanal, ethyl vanillin, phenylacetaldehyde, nonadiene-2,6-aldehyde, 2,6-dimethyl-2,6-octadienal, vanillin, citronellal, neral, hydroxymethylpentylcyclohexene acetal, p-diethylaminobenzaldehyde and undecenal.
[0069] In the present invention, the ketone compound may be at least one of an aliphatic ketone having a carbon number greater than or equal to 8 and an aromatic ketone having a carbon number greater than or equal to 8. Preferably, the ketone compound is at least one of an aliphatic ketone of C8-C11 and an aromatic ketone of C8-C14. Specifically, the ketone compound is selected from at least one of 6-methyl-3,5-heptadien-2-one, 2-undecanone, acetophenone, ionone, irone, methylionone, damascone and dihydrodamascone.
[0070] In the present invention, the alcohol compound is an alcohol having more than 6 carbon atoms, preferably an alcohol of C7-C15. Specifically, the alcohol compound is at least one of cinnamyl alcohol, menthol, cis-3,7-dimethyl-2,6-octadienol, citronellol, geraniol, myrcenol, 2,6,10-trimethyl-2,6,10-dodecatrien-12-ol, lavandulol, benzylenol, 2-phenylethanol, dihydromyrcenol, tetrahydrogeraniol and nerolidol.
[0071] In the present invention, the phenolic compound is a phenol having carbon atoms greater than or equal to 6, preferably a C6-C15 phenol. Specifically, the phenolic compound is at least one of thymol, ethyl maltol, methyl maltol, 3-propenyl-6-ethoxyphenol and isoeugenol.
[0072] In the present invention, the ester compound is an ester having a carbon number greater than 7, preferably an ester of C8-C17. Specifically, the ester compound is at least one of methyl salicylate, methyl cinnamate, ethyl cinnamate, ethyl phenylacetate, methyl phenylacetate, geranyl phenylacetate, phenylethyl phenylacetate, isoamyl phenylacetate, benzyl salicylate, p-methylbenzyl acetate, benzyl acetate, isobutyl benzoate, isoamyl salicylate, benzyl cinnamate, phenylethyl cinnamate, linalyl formate, linalyl acetate, linalyl isobutyrate, menthyl acetate, pine acetate and bornyl acetate.
[0073] In the asphalt additive of the present invention, in a preferred case, the active component in the first microcapsule is selected from aldehyde compounds and ketone compounds, the active component in the second microcapsule is selected from alcohol compounds and phenol compounds, and the active component in the third microcapsule is selected from ester compounds. The active components in various microcapsules are configured in this way, so that different active components are released at different sustained-release rates, which has a significantly better effect on inhibiting the emission of asphalt smoke.
[0074] In the asphalt additive of the present invention, in a preferred case, the mass ratio of the first microcapsule, the second microcapsule and the third microcapsule is 1:(0.25-4):(0.25-4).
[0075] The asphalt composition of the present invention contains asphalt and the asphalt additive described above. In the asphalt composition of the present invention, the addition of the asphalt additive makes it have a longer storage and service life, and can effectively reduce the emission of asphalt fume and reduce pollution to the environment during the construction process.
[0076] In the asphalt composition of the present invention, the content of the microcapsules may be 0.1-2 parts by weight, preferably 0.15-0.6 parts by weight, relative to 100 parts by weight of the asphalt.
[0077] In the present invention, the asphalt composition may further contain an antioxidant. The content of the antioxidant may be a conventional choice in the art. Specifically, relative to 100 parts by weight of the asphalt, the content of the antioxidant may be 0.01-0.1 parts by weight, preferably 0.02-0.08 parts by weight.
[0078] In the asphalt composition of the present invention, the asphalt can be at least one of straight-run asphalt, polymer-modified asphalt and natural asphalt. Preferably, the needle penetration of the asphalt is 30-2101 / 10mm.
[0079] In the asphalt composition of the present invention, the antioxidant can be a conventional choice in the art. Preferably, the antioxidant is bis(3,5-tri-tert-butyl-4-hydroxyphenyl) sulfide, p-tert-butyl catechol, 3,5-di-tert-butyl-4-hydroxybenzyl diethylphosphonate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 4,4'-thiobis(6-tert-butyl-3-methylphenol), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 1,3,5 - At least one of trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 2,6-di-tert-butyl-p-methylphenol, 3,5-di-tert-butyl-4-hydroxybenzoic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylic acid, 3-(3,5-dimethyl-4-hydroxyphenyl)acrylic acid, 3-(3,5-dimethoxy-4-hydroxyphenyl)acrylic acid and 3-(3-methoxy-4-hydroxyphenyl)acrylic acid.
[0080] The preparation method of the above-mentioned asphalt composition may include:
[0081] (1) The first microcapsule, the second microcapsule and the third microcapsule are prepared respectively, and the preparation process is as follows:
[0082] S1, mixing the active ingredient, emulsifier and water to form an oil-in-water emulsion;
[0083] S2, reacting the oil-in-water emulsion with a resin prepolymer, and then filtering, washing, and drying to obtain a pre-coated material;
[0084] S3, in the presence of a volatile solvent, mixing the rubber material with the pre-coated material, then mixing the obtained mixture with water, and heating until the volatile solvent evaporates to obtain microcapsules;
[0085] (2) Mixing molten asphalt, the first microcapsules, the second microcapsules, the third microcapsules and an optional antioxidant.
[0086] In step S1, the mixing process can be carried out in a shearing machine, and the operating conditions may include: a rotation speed of 2000-4000 r / min and a time of 20-30 min.
[0087] In step S1, the mass ratio of the active component, the emulsifier and water can be 1:(0.05-0.09):(6-9).
[0088] In some embodiments, the operation process of step S1 is: dissolving the active component in water, then adding the emulsifier, and then performing high-speed shear emulsification at a rotation speed of 2000-4000 r / min.
[0089] In step S2, before the oil-in-water emulsion reacts with the resin prepolymer, the pH value of the oil-in-water emulsion is adjusted to below 5, preferably 2 to 4. The reagent used to adjust the pH value can be a conventional inorganic acid solution, such as dilute hydrochloric acid.
[0090] In step S2, the reaction of the oil-in-water emulsion and the resin prepolymer is carried out under stirring. The stirring speed may be 400-800 r / min, the reaction temperature may be 60-90° C., and the reaction time may be 1-5 h.
[0091] In step S2, the filtering process may be suction filtration.
[0092] In step S2, the washing process may include washing with water and ethanol twice or more respectively.
[0093] In step S2, the drying process can be carried out in an oven, the drying temperature can be 60-90°C, and the drying time can be 5-10 hours.
[0094] In step S2, the resin prepolymer may be one or more of a melamine resin prepolymer, a urea-formaldehyde resin prepolymer and a polymethyl methacrylate prepolymer. In a preferred case, the resin prepolymer is a melamine resin prepolymer. The preparation method of the melamine resin prepolymer may include: mixing and dissolving melamine and formaldehyde solution with water, adjusting the pH value to 7.5-9.5, and then placing it in a constant temperature water bath at 60-90°C, and reacting for 0.5-3.5h under stirring. In the preparation process of the melamine resin prepolymer, the concentration of the formaldehyde solution may be 30-40wt.%. The mass ratio of the amount of melamine, the formaldehyde solution and water may be 1:(2-3):(8-10).
[0095] In step S3, the mass ratio of the rubber material, the volatile solvent and water may be 1:(10-20):(50-150).
[0096] In the method of the present invention, the active component can be selected from one or any combination of at least two of aldehyde compounds, ketone compounds, alcohol compounds, phenolic compounds and ester compounds. Specifically, the aldehyde compounds, ketone compounds, alcohol compounds, phenolic compounds and ester compounds are selected from the same materials as described above.
[0097] In the method of the present invention, the rubber material may be at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
[0098] In the method described in the present invention, the emulsifier can be selected from at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyldimethylhydroxyethylammonium chloride, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether and hexadecane polyoxyethylene ether.
[0099] In the method of the present invention, the volatile solvent can be selected from at least one of carbon tetrachloride, dichloromethane and trichloroethylene.
[0100] The asphalt additive and asphalt composition and the preparation method thereof of the present invention are further described by way of examples. The examples are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0101] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0102] Example 1
[0103] (1) 1 part by weight of 3,4-methylenedioxybenzaldehyde was added to 9 parts by weight of water at 60° C., and 0.05 parts by weight of hexadecyltrimethylammonium bromide was added. The mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion L-A1 in the aqueous phase.
[0104] 1 part by weight of myrcenol was added to 9 parts by weight of water at 60° C., and 0.05 parts by weight of hexadecyltrimethylammonium bromide was added. The mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion L-A2 in the aqueous phase.
[0105] 1 part by weight of ethyl cinnamate was added to 9 parts by weight of water at 60°C, and 0.05 parts by weight of hexadecyltrimethylammonium bromide was added. The mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion L-A3 in the aqueous phase.
[0106] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 8 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8.5, and then placed in a constant temperature water bath at 60° C. and stirred at 800 r / min for 0.5 h to obtain a melamine resin prepolymer.
[0107] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-A1 to adjust the pH value to 2, and 0.10 part by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain the pre-coated material Y-A1.
[0108] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-A2 to adjust the pH value to 2, and 0.12 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain the pre-coated material Y-A2.
[0109] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-A3 to adjust the pH value to 2, and 0.17 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain the pre-coated material Y-A3.
[0110] (3) Dissolve 0.1 parts by weight of chlorinated rubber in 1 part by weight of dichloromethane, add 1.00 parts by weight of the pre-coated material Y-A1, and stir and mix thoroughly. Add the obtained mixture to 5 parts by weight of water, stir at 500 r / min, and increase the temperature until the solvent evaporates to obtain microcapsules W-A1, which have a size of 3-5 μm, an elastic modulus of 0.5 GPa, and a capsule wall thickness of 1.2 μm, which conforms to the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 45wt.%, the content of capsule wall was 55wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 5:1.
[0111] 0.1 parts by weight of chlorinated rubber was dissolved in 1 part by weight of dichloromethane, and 0.55 parts by weight of the pre-coated material Y-A2 was added and stirred thoroughly. The obtained mixture was added to 5 parts by weight of water, stirred at 500 r / min, and the temperature was increased until the solvent evaporated to obtain microcapsules W-A2, which had a size of 5-7 μm, an elastic modulus of 0.9 GPa, and a capsule wall thickness of 2.1 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it is known that the content of capsule core in the microcapsule is 38wt.%, the content of capsule wall is 62wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 3:1.
[0112] 0.1 parts by weight of chlorinated rubber was dissolved in 1 part by weight of dichloromethane, and 0.43 parts by weight of the pre-coated material Y-A3 was added, and the mixture was stirred thoroughly. The obtained mixture was added to 5 parts by weight of water, stirred at 500 r / min, and the temperature was increased until the solvent evaporated to obtain microcapsules W-A3, which had a size of 7-9 μm, an elastic modulus of 2.2 GPa, and a capsule wall thickness of 3.1 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 30wt.%, the content of capsule wall was 70wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 2.7:1.
[0113] (4) Add 0.2 parts by weight of the prepared microcapsule W-A1, 0.05 parts by weight of the microcapsule W-A2, 0.1 parts by weight of the microcapsule W-A3 and 0.1 parts by weight of 3-(3,5-dimethyl-4-hydroxyphenyl)acrylic acid to 100 parts by weight of straight-run asphalt (needle penetration 70 1 / 10 mm), heat at 150°C and stir at 800 r / min for 3 hours to obtain an asphalt composition P1.
[0114] Example 2
[0115] (1) Add 1 part by weight of ionone to 7 parts by weight of water at 60° C., add 0.06 parts by weight of nonylphenol polyoxyethylene ether, and use a shearing machine at 2500 r / min to shear and emulsify for 25 minutes to form an oil-in-water emulsion L-B1 in the aqueous phase.
[0116] 1 part by weight of myrcenol was added to 7 parts by weight of water at 60° C., and 0.06 parts by weight of nonylphenol polyoxyethylene ether was added. The mixture was sheared and emulsified at 2500 r / min for 25 minutes to form an oil-in-water emulsion L-B2 in the aqueous phase.
[0117] 1 part by weight of phenylethyl cinnamate was added to 7 parts by weight of water at 60°C, and 0.06 parts by weight of nonylphenol polyoxyethylene ether was added. The mixture was sheared and emulsified at 2500 r / min for 25 minutes to form an oil-in-water emulsion L-B3 in the aqueous phase.
[0118] (2) 1 part by weight of melamine, 3 parts by weight of a 37 wt.% formaldehyde solution and 10 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 7.5, and then placed in a constant temperature water bath at 80° C. and stirred at 600 r / min for 1 hour to obtain a melamine resin prepolymer.
[0119] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-B1 to adjust the pH value to 4, and 0.12 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 600 r / min, and reacted at 70°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 70°C for 8 hours to obtain the pre-coated material Y-B1.
[0120] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-B2 to adjust the pH value to 4, and 0.17 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 600 r / min, and reacted at 70°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 70°C for 8 hours to obtain the pre-coated material Y-B2.
[0121] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-B3 to adjust the pH value to 4, and 0.22 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 600 r / min, and reacted at 70°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 70°C for 8 hours to obtain the pre-coated material Y-B3.
[0122] (3) 0.15 parts by weight of chloroprene rubber was dissolved in 3 parts by weight of carbon tetrachloride, and 1.40 parts by weight of the pre-coated material Y-B1 was added, and the mixture was stirred thoroughly. The obtained mixture was added to 10 parts by weight of water, stirred at 600 r / min, and the temperature was increased until the solvent evaporated to obtain microcapsules W-B1, which had a size of 2-4 μm, an elastic modulus of 0.6 GPa, and a capsule wall thickness of 0.7 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 46wt.%, the content of capsule wall was 54wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 4.6:1.
[0123] 0.15 parts by weight of chloroprene rubber was dissolved in 3 parts by weight of carbon tetrachloride, and 0.80 parts by weight of the pre-coated material Y-B2 was added and stirred thoroughly. The obtained mixture was added to 10 parts by weight of water, stirred at 600 r / min, and the temperature was increased until the solvent evaporated to obtain microcapsules W-B2, which had a size of 5-7 μm, an elastic modulus of 0.9 GPa, and a capsule wall thickness of 2.1 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 36wt.%, the content of capsule wall was 64wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 3.1:1.
[0124] 0.15 parts by weight of chloroprene rubber was dissolved in 3 parts by weight of carbon tetrachloride, and 0.70 parts by weight of the pre-coated material Y-B3 was added and stirred thoroughly. The obtained mixture was added into 10 parts by weight of water, stirred at 600 r / min, and the temperature was raised until the solvent evaporated to obtain microcapsules W-B3, which had a size of 7-9 μm, an elastic modulus of 2.4 GPa, and a capsule wall thickness of 3.2 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 30wt.%, the content of capsule wall was 70wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 3.0:1.
[0125] (4) Add 0.05 parts by weight of the prepared microcapsule W-B1, 0.2 parts by weight of the microcapsule W-B2, 0.1 parts by weight of the microcapsule W-B3 and 0.05 parts by weight of 3,5-di-tert-butyl-4-hydroxybenzyl diethylphosphonate to 100 parts by weight of straight-run asphalt (needle penetration 70 1 / 10 mm), heat at 140°C and stir at 900 r / min for 3 hours to obtain an asphalt composition P2.
[0126] Example 3
[0127] (1) 0.5 parts by weight of 2,6-dimethyl-2,6-octadienal and 0.5 parts by weight of neral were added to 6 parts by weight of water at 60° C., and 0.09 parts by weight of octylphenol polyoxyethylene ether were added. The mixture was emulsified at 3000 r / min using a shearing machine for 20 minutes to form an oil-in-water emulsion L-C1 in the aqueous phase.
[0128] 1 part by weight of dihydromyrcenol was added to 6 parts by weight of water at 60° C., and 0.09 parts by weight of octylphenol polyoxyethylene ether was added. The mixture was sheared and emulsified at 3000 r / min for 20 minutes to form an oil-in-water emulsion L-C2 in the aqueous phase.
[0129] 1 part by weight of linalyl formate was added to 6 parts by weight of water at 60° C., and 0.09 parts by weight of octylphenol polyoxyethylene ether was added. The mixture was sheared and emulsified at 3000 r / min for 20 minutes to form an oil-in-water emulsion L-C3 in the aqueous phase.
[0130] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 9 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8, and then placed in a constant temperature water bath at 70° C. and stirred at 500 r / min for 2 h to obtain a melamine resin prepolymer.
[0131] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-C1 to adjust the pH value to 3, and 0.14 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 500 r / min, and reacted at 65°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 90°C for 6 hours to obtain the pre-coated material Y-C1.
[0132] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-C2 to adjust the pH value to 3, and 0.18 part by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 500 r / min, and reacted at 65°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 90°C for 6 hours to obtain the pre-coated material Y-C2.
[0133] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-C3 to adjust the pH value to 3, and 0.28 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 500 r / min, and reacted at 65°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 90°C for 6 hours to obtain the pre-coated material Y-C3.
[0134] (3) 0.2 parts by weight of styrene-butadiene rubber was dissolved in 3 parts by weight of dichloromethane, and 1.34 parts by weight of the pre-coated material Y-C1 was added, and the mixture was stirred thoroughly. The obtained mixture was added into 25 parts by weight of water, stirred at 700 r / min, and the temperature was raised until the solvent evaporated, and microcapsules W-C1 were obtained, whose size was 3-5 μm, elastic modulus was 0.6 GPa, and capsule wall thickness was 1.3 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 44wt.%, the content of capsule wall was 56wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 3.3:1.
[0135] 0.2 parts by weight of styrene-butadiene rubber was dissolved in 3 parts by weight of dichloromethane, and 0.90 parts by weight of the pre-coated material Y-C2 was added, and the mixture was stirred thoroughly. The obtained mixture was added into 25 parts by weight of water, stirred at 700 r / min, and the temperature was raised until the solvent evaporated, and microcapsules W-C2 were obtained, whose size was 5-7 μm, elastic modulus was 1.1 GPa, and capsule wall thickness was 2.3 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 36wt.%, the content of capsule wall was 64wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 2.5:1.
[0136] 0.2 parts by weight of styrene-butadiene rubber was dissolved in 3 parts by weight of dichloromethane, and 0.85 parts by weight of the pre-coated material Y-C3 was added and stirred thoroughly. The obtained mixture was added into 25 parts by weight of water, stirred at 700 r / min, and the temperature was raised until the solvent evaporated to obtain microcapsules W-C3, which had a size of 7-9 μm, an elastic modulus of 2.7 GPa, and a capsule wall thickness of 3.4 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 27wt.%, the content of capsule wall was 73wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 2.8:1.
[0137] (4) Add 0.1 parts by weight of the prepared microcapsule W-C1, 0.1 parts by weight of the microcapsule W-C2, 0.2 parts by weight of the microcapsule W-C3, 0.05 parts by weight of 2,6-di-tert-butyl-p-methylphenol, and 0.05 parts by weight of bis(3,5-tri-tert-butyl-4-hydroxyphenyl) sulfide to 100 parts by weight of SBS modified asphalt (penetration 60 1 / 10 mm), heat at 170°C, and stir at 500 r / min for 1 hour to obtain asphalt composition P3.
[0138] Example 4
[0139] (1) 1 part by weight of p-methoxybenzaldehyde was added to 8 parts by weight of water at 60° C., and 0.06 parts by weight of sodium dodecylbenzenesulfonate was added. The mixture was sheared and emulsified at 4000 r / min for 20 minutes to form an oil-in-water emulsion L-D1 in the aqueous phase.
[0140] 1 part by weight of thymol was added to 8 parts by weight of water at 60°C, and 0.06 parts by weight of sodium dodecylbenzenesulfonate was added. The mixture was sheared and emulsified at 4000 r / min for 20 minutes to form an oil-in-water emulsion L-D2 in the aqueous phase.
[0141] 1 part by weight of methyl phenylacetate was added to 8 parts by weight of water at 60°C, and 0.06 parts by weight of sodium dodecylbenzenesulfonate was added. The mixture was sheared and emulsified at 4000 r / min for 20 minutes to form an oil-in-water emulsion L-D3 in the aqueous phase.
[0142] (2) 1 part by weight of melamine, 3 parts by weight of a 37 wt.% formaldehyde solution and 9 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 7.5, and then placed in a constant temperature water bath at 60° C. and stirred at 700 r / min for 2 h to obtain a melamine resin prepolymer.
[0143] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-D1 to adjust the pH value to 3, and 0.11 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 500 r / min, and reacted at 60°C for 5 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 90°C for 6 hours to obtain the pre-coated material Y-D1.
[0144] Add dilute hydrochloric acid to 1 part by weight of the oil-in-water emulsion L-D2 to adjust the pH value to 3, slowly add 0.15 part by weight of the prepared melamine resin prepolymer to the oil-in-water emulsion, stir at 500 r / min, and react at 60°C for 5 hours. After the reaction, filter the obtained mixed solution, wash it twice with water and ethanol respectively, and dry it in an oven at 90°C for 6 hours to obtain the pre-coated material Y-D2.
[0145] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-D3 to adjust the pH value to 3, and 0.21 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 500 r / min, and reacted at 60°C for 5 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 90°C for 6 hours to obtain the pre-coated material Y-D3.
[0146] (3) 0.17 parts by weight of chlorinated rubber was dissolved in 1.7 parts by weight of dichloromethane, and 1.69 parts by weight of the pre-coated material Y-D1 was added, and the mixture was stirred thoroughly. The obtained mixture was added to 18 parts by weight of water, stirred at 800 r / min, and the temperature was increased until the solvent evaporated to obtain microcapsules W-D1, which had a size of 3-5 μm, an elastic modulus of 0.5 GPa, and a capsule wall thickness of 1.2 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 46wt.%, the content of capsule wall was 54wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 4.9:1.
[0147] 0.17 parts by weight of chlorinated rubber was dissolved in 1.7 parts by weight of dichloromethane, and 0.80 parts by weight of the pre-coated material Y-D2 was added, and the mixture was fully stirred and mixed. The obtained mixture was added to 18 parts by weight of water, stirred at 800 r / min, and the temperature was increased until the solvent evaporated to obtain microcapsules W-D2, which had a size of 5-7 μm, an elastic modulus of 1.2 GPa, and a capsule wall thickness of 2.4 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 35wt.%, the content of capsule wall was 65wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 2.7:1.
[0148] 0.17 parts by weight of chlorinated rubber was dissolved in 1.7 parts by weight of dichloromethane, and 0.70 parts by weight of the pre-coated material Y-D3 was added, and the mixture was stirred thoroughly. The obtained mixture was added to 18 parts by weight of water, stirred at 800 r / min, and the temperature was increased until the solvent evaporated to obtain microcapsules W-D3, which had a size of 7-9 μm, an elastic modulus of 2.5 GPa, and a capsule wall thickness of 3.3 μm, which met the calculation formula Y = 0.42X 2 -0.92X+T. Through detection, it was found that the content of capsule core in the microcapsule was 28wt.%, the content of capsule wall was 72wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 2.7:1.
[0149] (4) Add 0.1 parts by weight of the prepared microcapsules W-D1, 0.2 parts by weight of the microcapsules W-D2, 0.2 parts by weight of the microcapsules W-D3, 0.05 parts by weight of 3,5-di-tert-butyl-4-hydroxybenzyl diethylphosphonate and 0.05 parts by weight of p-tert-butylcatechol to 100 parts by weight of straight-run asphalt (penetration 70 1 / 10 mm) in natural asphalt (penetration 50 1 / 10 mm), heat at 160°C and stir at 800 r / min for 2 hours to obtain asphalt composition P4.
[0150] Example 5
[0151] (1) 1 part by weight of methyl ionone was added to 7 parts by weight of water at 60° C., and 0.08 parts by weight of hexadecyltrimethylammonium chloride was added. The mixture was sheared and emulsified at 3000 r / min for 30 minutes to form an oil-in-water emulsion L-E1 in the aqueous phase.
[0152] 1 part by weight of 3-propenyl-6-ethoxyphenol was added to 7 parts by weight of water at 60°C, and 0.08 parts by weight of hexadecyltrimethylammonium chloride was added. The mixture was sheared and emulsified at 3000 r / min for 30 minutes to form an oil-in-water emulsion L-E2 in the aqueous phase.
[0153] 1 part by weight of pine acetate was added to 7 parts by weight of water at 60°C, and 0.08 parts by weight of hexadecyltrimethylammonium chloride was added. The mixture was sheared and emulsified at 3000 r / min for 30 minutes to form an oil-in-water emulsion L-E3 in the aqueous phase.
[0154] (2) 1 part by weight of melamine, 2 parts by weight of a 37% formaldehyde solution and 9 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8, and then the flask was placed in a constant temperature water bath at 90° C. and stirred at 400 r / min for 3.5 hours to obtain a melamine resin prepolymer.
[0155] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-E1 to adjust the pH value to 2, and 0.10 part by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 800 r / min, and reacted at 90°C for 1 hour. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 9 hours to obtain the pre-coated material Y-E1.
[0156] Add dilute hydrochloric acid to 1 part by weight of the oil-in-water emulsion L-E2 to adjust the pH value to 2, slowly add 0.15 part by weight of the prepared melamine resin prepolymer to the oil-in-water emulsion, stir at 800 r / min, and react at 90°C for 1 hour. After the reaction, filter the obtained mixed solution, wash it twice with water and ethanol respectively, and place it in an oven at 60°C for 9 hours to obtain the pre-coated material Y-E2.
[0157] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-E3 to adjust the pH value to 2, and 0.22 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 800 r / min, and reacted at 90°C for 1 hour. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 9 hours to obtain the pre-coated material Y-E3.
[0158] (3) Dissolve 0.25 parts by weight of chlorinated rubber in 5 parts by weight of dichloromethane, add 1.48 parts by weight of the pre-coated material Y-E1, and stir and mix thoroughly. Add the obtained mixture to 30 parts by weight of water, stir at 700r / min, and increase the temperature until the solvent evaporates to obtain microcapsules W-E1, which have a size of 3-5μm, an elastic modulus of 0.6GPa, and a capsule wall thickness of 0.8μm, which conforms to the calculation formula Y=0.42X2-0.92X+T. Through detection, it is known that the content of the capsule core in the microcapsule is 48wt.%, the content of the capsule wall is 52wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 2.6:1.
[0159] Dissolve 0.25 parts by weight of chlorinated rubber in 5 parts by weight of dichloromethane, add 1.37 parts by weight of the pre-coated material Y-E2, and stir and mix thoroughly. Add the obtained mixture to 30 parts by weight of water, stir at 700r / min, increase the temperature until the solvent evaporates, and obtain microcapsules W-E2, which have a size of 5-7μm, an elastic modulus of 1.0GPa, and a capsule wall thickness of 2.2μm, which conforms to the calculation formula Y=0.42X2-0.92X+T. Through detection, it is known that the content of the capsule core in the microcapsule is 37wt.%, the content of the capsule wall is 63wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 2.6:1.
[0160] Dissolve 0.25 parts by weight of chlorinated rubber in 5 parts by weight of dichloromethane, add 0.98 parts by weight of the pre-coated material Y-E3, and stir and mix thoroughly. Add the obtained mixture to 30 parts by weight of water, stir at 700r / min, increase the temperature until the solvent evaporates, and obtain microcapsules W-E3, whose size is 7-9μm, elastic modulus is 2.4GPa, and capsule wall thickness is 3.2μm, which conforms to the calculation formula Y=0.42X2-0.92X+T. Through detection, it is known that the content of capsule core in the microcapsule is 29wt.%, the content of capsule wall is 71wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 2.5:1.
[0161] (4) Add 0.2 parts by weight of the prepared microcapsules W-E1, 0.2 parts by weight of the microcapsules W-E2, 0.2 parts by weight of the microcapsules W-E3, 0.05 parts by weight of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylic acid, and 0.05 parts by weight of 3-(3,5-dimethyl-4-hydroxyphenyl)acrylic acid to 100 parts by weight of straight-run asphalt (needle penetration 70 1 / 10 mm), heat at 140°C, and stir at 1000 r / min for 3 hours to obtain asphalt composition P5.
[0162] Comparative Example 1
[0163] An asphalt composition was prepared according to the method of Example 5, except that the microcapsules W-E2 and the microcapsules W-E3 in step (4) were replaced by the microcapsules W-E1 of the same weight, to obtain an asphalt composition D1.
[0164] Comparative Example 2
[0165] An asphalt composition was prepared according to the method of Example 5, except that the microcapsules W-E1 and W-E3 in step (4) were replaced by the microcapsules W-E2 of the same weight to obtain an asphalt composition D2.
[0166] Comparative Example 3
[0167] An asphalt composition was prepared according to the method of Example 5, except that the microcapsules W-E1 and W-E2 in step (4) were replaced by the microcapsules W-E3 of the same weight to obtain an asphalt composition D3.
[0168] Comparative Example 4
[0169] (Comparison between this comparative example and Example 1)
[0170] 0.09 parts by weight of 3,4-methylenedioxybenzaldehyde, 0.02 parts by weight of myrcenol, 0.03 parts by weight of ethyl cinnamate and 0.1 parts by weight of 3-(3,5-dimethyl-4-hydroxyphenyl)acrylic acid were added to 100 parts by weight of straight-run asphalt (needle penetration 701 / 10 mm), heated at 150°C and stirred at 800 r / min for 3 hours to obtain asphalt composition D4.
[0171] Comparative Example 5
[0172] (Comparison between this comparative example and Example 1)
[0173] (1) 1 part by weight of 3,4-methylenedioxybenzaldehyde was added to 9 parts by weight of water at 60° C., and 0.05 parts by weight of hexadecyltrimethylammonium bromide was added. The mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion L-A1 in the aqueous phase.
[0174] 1 part by weight of myrcenol was added to 9 parts by weight of water at 60° C., and 0.05 parts by weight of hexadecyltrimethylammonium bromide was added. The mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion L-A2 in the aqueous phase.
[0175] 1 part by weight of ethyl cinnamate was added to 9 parts by weight of water at 60°C, and 0.05 parts by weight of hexadecyltrimethylammonium bromide was added. The mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion L-A3 in the aqueous phase.
[0176] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 8 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8.5, and then placed in a constant temperature water bath at 60° C. and stirred at 800 r / min for 0.5 h to obtain a melamine resin prepolymer.
[0177] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-A1 to adjust the pH value to 2, and 0.10 part by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain the pre-coated material Y-A1.
[0178] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-A2 to adjust the pH value to 2, and 0.12 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain the pre-coated material Y-A2.
[0179] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-A3 to adjust the pH value to 2, and 0.17 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain the pre-coated material Y-A3.
[0180] (3) Add 0.2 parts by weight of the prepared pre-coated material Y-A1, 0.05 parts by weight of the pre-coated material Y-A2, 0.1 parts by weight of the pre-coated material Y-A3 and 0.1 parts by weight of 3-(3,5-dimethyl-4-hydroxyphenyl)acrylic acid to 100 parts by weight of straight-run asphalt (needle penetration 70 1 / 10 mm), heat at 150°C and stir at 800 r / min for 3 hours to obtain an asphalt composition D5.
[0181] Comparative Example 6
[0182] (Comparison between this comparative example and Example 1)
[0183] (1) 1 part by weight of 3,4-methylenedioxybenzaldehyde was added to 9 parts by weight of water at 60° C., and 0.05 parts by weight of hexadecyltrimethylammonium bromide was added. The mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion L-A1 in the aqueous phase.
[0184] 1 part by weight of myrcenol was added to 9 parts by weight of water at 60° C., and 0.05 parts by weight of hexadecyltrimethylammonium bromide was added. The mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion L-A2 in the aqueous phase.
[0185] 1 part by weight of ethyl cinnamate was added to 9 parts by weight of water at 60°C, and 0.05 parts by weight of hexadecyltrimethylammonium bromide was added. The mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion L-A3 in the aqueous phase.
[0186] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 8 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8.5, and then placed in a constant temperature water bath at 60° C. and stirred at 800 r / min for 0.5 h to obtain a melamine resin prepolymer.
[0187] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-A1 to adjust the pH value to 2, and 0.10 part by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain the pre-coated material Y-A1.
[0188] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-A2 to adjust the pH value to 2, and 0.12 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain the pre-coated material Y-A2.
[0189] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion L-A3 to adjust the pH value to 2, and 0.17 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain the pre-coated material Y-A3.
[0190] (3) 0.1 parts by weight of chlorinated rubber, 1.00 parts by weight of the pre-coated material Y-A1 and 5 parts by weight of water were mixed and stirred at 500 r / min to obtain microcapsules W-F1, wherein the chlorinated rubber in the microcapsules could not be wrapped in the outermost layer of the microcapsules in the form of a film, the size of which was 4-6 μm, the elastic modulus was 0.8 GPa, and the thickness of the capsule wall was 2.3 μm, which did not meet the calculation formula Y=0.42X 2 -0.92X+T.
[0191] 0.1 parts by weight of chlorinated rubber, 0.55 parts by weight of the pre-coated material Y-A2 and 5 parts by weight of water were mixed and stirred at 500 r / min to obtain microcapsules W-F2, wherein the chlorinated rubber in the microcapsules could not be wrapped in the outermost layer of the microcapsules in the form of a film, the size of which was 6-8 μm, the elastic modulus was 1.9 GPa, and the thickness of the capsule wall was 3.4 μm, which did not meet the calculation formula Y=0.42X 2 -0.92X+T.
[0192] 0.1 parts by weight of chlorinated rubber, 0.43 parts by weight of the pre-coated material Y-A3 and 5 parts by weight of water were mixed and stirred at 500 r / min to obtain microcapsules W-F3, wherein the chlorinated rubber in the microcapsules could not be wrapped in the outermost layer of the microcapsules in the form of a film, the size of which was 8-10 μm, the elastic modulus was 2.5 GPa, and the thickness of the capsule wall was 4.0 μm, which did not meet the calculation formula Y=0.42X 2 -0.92X+T.
[0193] (4) Add 0.2 parts by weight of the prepared microcapsule W-F1, 0.05 parts by weight of the microcapsule W-F2, 0.1 parts by weight of the microcapsule W-F3 and 0.1 parts by weight of 3-(3,5-dimethyl-4-hydroxyphenyl)acrylic acid to 100 parts by weight of straight-run asphalt (needle penetration 70 1 / 10 mm), heat at 150°C and stir at 800 r / min for 3 hours to obtain asphalt composition D6.
[0194] Comparative Example 7
[0195] (Comparison between this comparative example and Example 1)
[0196] Microcapsules were prepared according to the method of Example 1, except that in step (1), the amount of water was increased to 15 parts by weight, and the amount of chlorinated rubber was increased to 0.50 parts by weight.
[0197] The microcapsule W-G1 obtained has a size of 4-6 μm, an elastic modulus of 1.0 GPa, and a capsule wall thickness of 1.7 μm, which does not conform to the calculation formula Y = 0.42X 2 -0.92X+T.
[0198] The microcapsule W-G2 was obtained, with a size of 6-8 μm, an elastic modulus of 2.3 GPa, and a capsule wall thickness of 2.7 μm, which did not conform to the calculation formula Y = 0.42X 2 -0.92X+T.
[0199] The microcapsule W-G3 was obtained, with a size of 8-10 μm, an elastic modulus of 3.7 GPa, and a capsule wall thickness of 3.6 μm, which did not conform to the calculation formula Y = 0.42X 2 -0.92X+T.
[0200] (4) Add 0.2 parts by weight of the prepared microcapsule W-G1, 0.05 parts by weight of the microcapsule W-G2, 0.1 parts by weight of the microcapsule W-G3 and 0.1 parts by weight of 3-(3,5-dimethyl-4-hydroxyphenyl)acrylic acid to 100 parts by weight of straight-run asphalt (needle penetration 70 1 / 10 mm), heat at 150°C and stir at 800 r / min for 3 hours to obtain asphalt composition D7.
[0201] Test Example 1
[0202] Asphalt smoke tests were carried out using straight-run asphalt (needle penetration 70 1 / 10mm), natural asphalt (needle penetration 50 1 / 10mm), and SBS modified asphalt (needle penetration 60 1 / 10mm) as asphalt matrices and the asphalt compositions prepared in the above embodiments and comparative examples. Specifically, the asphalt smoke was enriched under heating conditions of 163°C for 6 hours, and the asphalt smoke was tested and analyzed using gas chromatography and a total hydrocarbon analyzer.
[0203] Table 1: Asphalt smoke test results
[0204]
[0205] It can be seen from the results in Table 1 that the asphalt additive and asphalt composition according to the present invention, by combining three microcapsules with different sustained-release rates, can achieve the release of different active components at different sustained-release rates, thereby effectively reducing the emission of asphalt fume and reducing pollution to the environment.
[0206] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An asphalt additive, characterized in that: The asphalt additive contains a first microcapsule, a second microcapsule and a third microcapsule, wherein the first microcapsule, the second microcapsule and the third microcapsule each include a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains active components, the capsule wall thickness of the first microcapsule is 0.5-2μm, the capsule wall thickness of the second microcapsule is greater than 2μm and less than or equal to 3μm, and the capsule wall thickness of the third microcapsule is greater than 3μm and less than or equal to 5μm.
2. The asphalt additive according to claim 1, characterized in that: The mass ratio of the first microcapsule, the second microcapsule and the third microcapsule is 1:(0.25-4):(0.25-4).
3. The asphalt additive according to claim 1 or 2, characterized in that: In the first microcapsule, the second microcapsule and the third microcapsule, the capsule wall comprises an inner wall layer and an outer wall layer, the inner wall layer is a resin, and the outer wall layer is a rubber material; Preferably, the mass ratio of the inner wall layer to the outer wall layer is 2.4-5:
1.
4. The asphalt additive according to claim 3, characterized in that: The resin is at least one of melamine resin, urea-formaldehyde resin and polymethyl methacrylate, preferably melamine resin.
5. The asphalt composition according to claim 3, characterized in that The rubber material is at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
6. The asphalt additive according to any one of claims 1 to 5, characterized in that: In the first microcapsule, the second microcapsule and the third microcapsule, the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula: Y = 0.42X 2 - 0.92X + T Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1; The elastic modulus of the microcapsule is obtained by testing the mechanical properties of the microcapsule using a nanoindenter, and the thickness of the capsule wall is obtained by testing the frozen sections of the microcapsule using a scanning electron microscope.
7. The asphalt additive according to any one of claims 1 to 6, characterized in that: In the first microcapsule, the mass ratio of the capsule core to the capsule wall is 1:0.9-1.5; in the second microcapsule, the mass ratio of the capsule core to the capsule wall is 1:1.5-2.2; in the third microcapsule, the mass ratio of the capsule core to the capsule wall is 1:2.2-3.
8. The asphalt additive according to any one of claims 1 to 7, characterized in that: The active component is an inhibitor for inhibiting the release of asphalt smoke, preferably at least one of aldehyde compounds, ketone compounds, alcohol compounds, phenol compounds and ester compounds; Preferably, the aldehyde compound is selected from aliphatic aldehydes having carbon atoms greater than or equal to 7 and aromatic aldehydes having carbon atoms greater than or equal to 6, more preferably at least one of p-tolualdehyde, decanal, o-carboxybenzaldehyde, p-isopropylbenzaldehyde, cinnamaldehyde, p-hydroxybenzaldehyde, p-methoxybenzaldehyde, 2-methyl-3-(3,4-methylene-dioxyphenyl)propanal, 3,4-methylenedioxybenzaldehyde, 3-(4-isopropylphenyl)-2-methylpropanal, ethyl vanillin, phenylacetaldehyde, anisaldehyde, nonadiene-2,6-aldehyde, 2,6-dimethyl-2,6-octadienal, vanillin, citronellal, neral, hydroxymethylpentylcyclohexene acetal, p-diethylaminobenzaldehyde and undecenal; Preferably, the ketone compound is selected from aliphatic ketones having carbon atoms greater than or equal to 8 and aromatic ketones having carbon atoms greater than or equal to 8, more preferably at least one of 6-methyl-3,5-heptadien-2-one, 2-undecanone, acetophenone, ionone, irone, methylionone, damascenone and dihydrodamascenone; Preferably, the alcohol compound is an alcohol having more than 6 carbon atoms, more preferably at least one of cinnamyl alcohol, menthol, cis-3,7-dimethyl-2,6-octadienol, citronellol, geraniol, myrcenol, 2,6,10-trimethyl-2,6,10-dodecatrien-12-ol, lavandulol, benzylenol, 2-phenylethanol, dihydromyrcenol, tetrahydrogeraniol and nerolidol; Preferably, the phenolic compound is a phenol having 6 or more carbon atoms, more preferably at least one of thymol, ethyl maltol, methyl maltol, 3-propenyl-6-ethoxyphenol and isoeugenol; Preferably, the ester compound is an ester having a carbon number greater than 7, more preferably at least one of methyl salicylate, methyl cinnamate, ethyl cinnamate, ethyl phenylacetate, methyl phenylacetate, geranyl phenylacetate, phenylethyl phenylacetate, isoamyl phenylacetate, benzyl salicylate, p-methylbenzyl acetate, benzyl acetate, isobutyl benzoate, isoamyl salicylate, benzyl cinnamate, phenylethyl cinnamate, linalyl formate, linalyl acetate, linalyl isobutyrate, menthyl acetate, pine acetate and bornyl acetate.
9. The asphalt additive according to claim 8, characterized in that: The active components in the first microcapsule are selected from aldehyde compounds and ketone compounds, the active components in the second microcapsule are selected from alcohol compounds and phenol compounds, and the active components in the third microcapsule are selected from ester compounds.
10. An asphalt composition, characterized in that: The asphalt composition contains asphalt and the asphalt additive according to any one of claims 1-9.
11. The asphalt composition according to claim 10, characterized in that Relative to 100 parts by weight of the asphalt, the content of the asphalt additive is 0.1-2 parts by weight, preferably 0.15-0.6 parts by weight.
12. The asphalt composition according to claim 10 or 11, characterized in that: The asphalt composition further contains an antioxidant, and the content of the antioxidant is 0.01-0.1 parts by weight relative to 100 parts by weight of the asphalt.
13. The asphalt composition according to claim 12, characterized in that The antioxidant is bis(3,5-tri-tert-butyl-4-hydroxyphenyl) sulfide, p-tert-butyl catechol, 3,5-di-tert-butyl-4-hydroxybenzyl diethylphosphonate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 4,4'-thiobis(6-tert-butyl-3-methylphenol), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-trimethylolpropionate, At least one of 2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 2,6-di-tert-butyl-p-methylphenol, 3,5-di-tert-butyl-4-hydroxybenzoic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylic acid, 3-(3,5-dimethyl-4-hydroxyphenyl)acrylic acid, 3-(3,5-dimethoxy-4-hydroxyphenyl)acrylic acid and 3-(3-methoxy-4-hydroxyphenyl)acrylic acid.
14. The asphalt composition according to any one of claims 10 to 13, characterized in that: The asphalt is at least one of straight-run asphalt, polymer-modified asphalt and natural asphalt; Preferably, the needle penetration of the asphalt is 30-210 1 / 10mm.
15. A method for preparing the asphalt composition according to any one of claims 10 to 14, characterized in that: The method includes: (1) The first microcapsule, the second microcapsule and the third microcapsule are prepared respectively, and the preparation process is as follows: S1, mixing the active ingredient, emulsifier and water to form an oil-in-water emulsion; S2, reacting the oil-in-water emulsion with a resin prepolymer, and then filtering, washing, and drying to obtain a pre-coated material; S3, in the presence of a volatile solvent, mixing the rubber material with the pre-coated material, then mixing the obtained mixture with water, and heating until the volatile solvent evaporates to obtain microcapsules; (2) Mixing molten asphalt, the first microcapsules, the second microcapsules, the third microcapsules and an optional antioxidant.
16. The method according to claim 15, characterized in that In step S1, the mass ratio of the active component, the emulsifier and water is 1:(0.05-0.09):(6-9).
17. The method according to claim 15, characterized in that In step S2, before the oil-in-water emulsion reacts with the resin prepolymer, the pH value of the oil-in-water emulsion is adjusted to below 5, preferably 2-4.
18. The method according to claim 15 or 17, characterized in that In step S2, the resin prepolymer is a melamine resin prepolymer; Preferably, the preparation method of the melamine resin prepolymer comprises: mixing and dissolving melamine and formaldehyde solution with water, adjusting the pH value to 7.5-9.5, and then placing in a constant temperature water bath at 60-90° C., and reacting for 0.5-3.5 hours under stirring; Preferably, the concentration of the formaldehyde solution is 30-40wt.%; Preferably, the mass ratio of the melamine, the formaldehyde solution and the water is 1:(2-3):(8-10).
19. The method according to claim 15, characterized in that In step S3, the mass ratio of the rubber material, the volatile solvent and water is 1:(10-20):(50-150).
20. The method according to any one of claims 15 to 19, characterized in that: The emulsifier is selected from at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyldimethylhydroxyethylammonium chloride, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether and hexadecane polyoxyethylene ether.
21. The method according to any one of claims 15 to 20, characterized in that: The volatile solvent is selected from at least one of carbon tetrachloride, dichloromethane and trichloroethylene.
Citation Information
Patent Citations
Method for reducing odor in bitumen
CN101842426A
Multi-layer microcapsule for room-temperature self repairing, and preparation method and application thereof
CN103242496A
Smoke suppressing and deodorizing additive, preparation method thereof and modified asphalt
CN109749466A
Application of slow release microcapsules to improvement of ageing resistance of asphalt
CN106398246A
Preparation method and application of asphalt concrete self-repairing microcapsule
CN114699996A
Cited By
Asphalt additive, and asphalt composition and preparation method therefor
EP4745197A1